Nursery area and size structure of the lemon shark population, Negaprion brevirostris (Poey, 1868), in Los Roques Archipelago National Park, Venezuela - Tavares, Rafael; 1. Centro de Ecología, Instituto Venezolano de Investigaciones Científicas (IVIC), Apdo. 20632, Caracas 1020-A, Venezuela. 2. Instituto Nacional de Investigaciones Agrícolas (INIA), La Asunción 6311, Isla de Margarita, Venezuela. 3. Centro para la Investigación de Tiburones (CIT), Av. Don Bosco, Qta ABC, No. 10, La Florida, Caracas 1050, Venezuela. (2016)
The protection of the habitats used by juvenile sharks is a management strategy that has recently caught the attention of fishery biologists. In the present study, we evaluated the population of the lemon shark (Negaprion brevirostris) from Los Roques Archipelago in order to identify the nursery area, describe the size composition, and examine the variation in nocturnal activity of the juvenile individuals. The data analysed came from three different sources: commercial shark fishery, tag-recapture sampling, and visual records. A total of 375 lemon sharks with total lengths between 55 and 281 cm were recorded during the study period. Overall data showed that the area occupied by juvenile lemon sharks was clearly partitioned into primary and secondary nurseries. Additionally, nighttime activity seemed to change according to the size of sharks in the primary nursery, suggesting a reduction of time activity overlapping among juveniles of distinct size/age. Results suggest that the strategy of utilization of the primary nurseries by the lemon shark may lead to important ecological benefits by reducing the competition, predation and natural mortality.